Effectiveness of Traditional Games In Stimulating Elementary School Student Motor Skill Development - Uray Gustian (Universitas Pendidikan Indonesia, 2021)
Motor skills are important skills that must be possessed by every student because it has an influence on the overall student development. However, various obstacles that affect the achievement of students' motor skills often occur during the implementation of motor skill learning. The purpose of this research was to find learning activities that can stimulate motor skills of elementary school students. Experiments were carried out using One-Group Pre-test Post-test Design. Participants of the study were 126 first grade elementary school students, consisting of 76 males and 50 females aged 6-6.5 years. The sampling technique used the total sampling method. The data collection technique used the Test of Gross Motor Skill-Second Edition (TGMD-2) with an observation sheet instrument. The analysis employed SPSS 20 with a paired sample test. The results showed that there was an increase in the post-test mean score compared to the pre-test mean score with a significant increase. This increase occurred because traditional games used a play-based approach and encouraged students to use their motor skills. For that reason, traditional games are effective in improving motor skills of elementary school students.